1997
DOI: 10.1086/647640
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Respiratory Syncytial Virus Infections Prevention and Control in Bone Marrow Transplant Patients

Abstract: Institution of a multifaceted infection control strategy significantly reduced the frequency of nosocomial RSV infection in a high-risk group of adult BMT recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 20 publications
0
31
0
1
Order By: Relevance
“…A similar strategy was shown to be efficient at controlling RSV outbreaks by Jones et al 19 This prompted the CDC to adopt these preventive strategies, adding URTI screening in visitors and health care workers, as well as a daily surveillance of upper and lower respiratory tract infection signs and symptoms in patients. 23 The TICP applied in our unit until 2001 was comparable with the measures adopted by Garcia et al, 18 with the significant differences being that TICP was applied all year round, reverse isolation was applied only in neutropenic patients (rather than in all HSCT recipients) and we did not cohort infected patients because each was already in a private room. Despite rigorous implementation and high compliance to TICP, we still observed occasional nosocomial transmission of RSV with dismal consequence for the infected patient.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…A similar strategy was shown to be efficient at controlling RSV outbreaks by Jones et al 19 This prompted the CDC to adopt these preventive strategies, adding URTI screening in visitors and health care workers, as well as a daily surveillance of upper and lower respiratory tract infection signs and symptoms in patients. 23 The TICP applied in our unit until 2001 was comparable with the measures adopted by Garcia et al, 18 with the significant differences being that TICP was applied all year round, reverse isolation was applied only in neutropenic patients (rather than in all HSCT recipients) and we did not cohort infected patients because each was already in a private room. Despite rigorous implementation and high compliance to TICP, we still observed occasional nosocomial transmission of RSV with dismal consequence for the infected patient.…”
Section: Discussionmentioning
confidence: 82%
“…Garcia et al 18 reported the first intervention field study on the prevention and control of nosocomial RSV on two dedicated HSCT wards from December to March. The program included rapid diagnosis (antigen detection), adequate handwashing and patient cohorting of documented RSV infection (transfer to another unit, cohort and contact isolation precautions with gloves, gowns and masks).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 However, ribavirin continues to be prescribed for treatment and prophylaxis of RSV in bone marrow transplant patients because of its reported clinical efficacy in this application. 2 Approximately six children per year receive ribavirin at Children's Hospital, and it is usually administered for 3-4 months at a time. The children receiving ribavirin at Denver Children's Hospital are typically several years old (average age: 7 years old).…”
Section: Introductionmentioning
confidence: 99%